Lipoxygenase Activity Accelerates Programmed Spore Germination in Aspergillus fumigatus - Fischer, Gregory J.; Bacon, William; Yang, Jun; Palmer, Jonathan M.; Dagenais, Taylor; Hammock, Bruce D.; Keller, Nancy P. (Frontiers in Microbiology, 2017)
The opportunistic human pathogen Aspergillus fumigatus initiates invasive growth through a programmed germination process that progresses from dormant spore to swollen spore to germling and ultimately invasive hyphal growth. We find a lipoxygenase with considerable homology to human Alox5 and Alox15, LoxB, that impacts the transitions of programmed spore germination. Overexpression of loxB (OE::loxB) increases germination with rapid advance to the germling stage. However, deletion of loxB (∆loxB) or its signal peptide only delays progression to the swollen spore stage in the presence of arachidonic acid (AA); no delay is observed in minimal media. This delay is remediated by the addition of the oxygenated AA oxylipin 5-hydroxyeicosatetraenoic acid (5-HETE) that is a product of human Alox5. We propose that A. fumigatus acquisition of LoxB (found in few fungi) enhances germination rates in polyunsaturated fatty acid-rich environments.